Study of 22 Children Friendly Public Health Center Bekasi City 2020 - Mas Wishnuwardhana; Kevin Christian Sembiring; Vania Novita; Ivana Ester; Joue Abraham Trixie; Benedikta Suryandari (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: Indonesia has a target to achieve Indonesia Layak Anak (IDOLA) predicate by 2030. Public health center has a very important role in realizing this target because public health center are the front guard for child protection in the health sector. This study aimed to know the overview of evaluation on the assessment of Children Friendly Public Health Center for the preparation of Indonesia Layak Anak 2030.Method: This type of this research is descriptive study. This report was conducted on the assessment of 22 Children Friendly Public Health Center on Bekasi city. The data was collected from the assessment and represented using Microsoft excel 2019.Results: Based on the total score obtained, the public health center with a total score of 965 was Karang Kitri Health Center, followed by Bojong Rawa Lumbu Health Center with a total score of 900 and Perumnas 2 Health Center with a total score of 89. There are still many public health center that do not meet the indicators and get maximum scores.Conclusion: This is the task of improving performance and facilities, to get maximum value and to be part of achieving the target for Indonesia as a Indonesia Layak Anak by 2030.